Anthropometric and Psychomotor Development Factors Linked to Foot Valgus in Children Aged 6 to 9 Years - Morales-Asencio, José Miguel; Medina-Alcántara, Francisco Miguel; Ortega-Ávila, Ana Belén; Jiménez-Cebrián, Ana María; Páez-Moguer, Joaquín; Cervera-Marín, José Antonio; Gijón-Noguerón, Gabriel (American Podiatric Medical Association, 2019)
Background: Planovalgus foot prevalence estimates vary widely (0.6%-77.9%). Among the many factors that may influence planovalgus foot development, much attention has been given to body mass index, especially that of children's feet; factors related to psychomotor development have been less studied. We sought to determine the presence of planovalgus foot in children and its association with anthropometric parameters and psychomotor development. Methods: A case-control study was conducted in Málaga, Spain, 2012-2013, of 104 schoolchildren (mean ± SD age, 7.55 ± 0.89 years; 45.2% were boys). Age, sex, body mass index, presence of valgus (valgus index, by pedigraphy), and personal history related to psychomotor development of the lower limbs (presence/absence of crawling, age at onset of crawling, age at onset of walking, use of mobility aids) were evaluated. Results: Of the children with obesity, 53.7% had valgus deformity in the left hindfoot (odds ratio [OR], 6.94; 95% confidence interval [CI], 2.72-17.70; P < .0001). In the right foot, the corresponding values were 54.5% (OR, 9.08; 95% CI, 3.38-24.36; P < .0001). Multivariate logistic regression showed an increased risk of left planovalgus foot in boys, in children with overweight or obesity, and in those who began walking later. For the right foot, the same risk factors applied except age at onset of walking. Conclusions: These results corroborate data from previous studies, which report an association between overweight and obesity and the onset of planovalgus foot in children. In addition, we identify a new risk factor: age at onset of walking.
Keywords: Pies - Anomalías y malformaciones; Foot valgus; Children; Anthropometric; Psychomotor Development